Perendaman menggunakan Air Panas di Media Murashige dan Skoog pada Uji Viabilitas Benih Bawang Merah (Allium cepa L.) - Khair, Hadriman; Yusuf, Mukhtar; Shafhah, Atikah (Lembaga Riset Mutiara Akbar, 2024)
In this research, a viability test was carried out to obtain information about the ability of shallots to germinate under certain conditions. The use of hot water in Murashige and Skog media is a way to obtain information on certain conditions. The aim of this research is to determine the effect of hot water immersion temperature and water soaking time on the viability of shallot seeds (Allium cepa L.) on Murashige and Skog media. This research was carried out at the Alifa Agricultural Research Center (AARC) Laboratory. This research used a completely randomized factorial design (RAL) with two factors, the first factor was hot water temperature with 3 levels, namely: S0 = 27 ? C (control), S1 = 45 ? C, S2 = 60 ? C. The second factor is the length of immersion with 3 levels, namely: L0 = 3 seconds (control), L1 = 10 minutes, L2 = 15 minutes, a combination of 9 treatments which were repeated 3 times to obtain 27 experimental units. The number of samples in each experiment was 3, so the total sample was 81. The parameters measured were the percentage of plumule emergence (%), the percentage of radicle emergence (%), the percentage of live explants (%), the percentage of explants contaminated with bacteria (%), the percentage of explants contaminated with fungi (%), the number of shoots (plants), the height of plants (cm), number of leaves and number of roots. The results showed that the observed heat treatment had no significant effect on the observed parameters of the percentage of explants contaminated with bacteria, the percentage of explants contaminated with fungi, and the number of roots. In the long soaking treatment, it was observed that it had a significant effect on the percentage of live explants. The interaction of temperature treatment and soaking time had a significant effect on the percentage of live explants.